LABELISASI HALAL DAN HARAM - Desy Kristiane (Tadayun: Jurnal Hukum Ekonomi Syariah, 2021)
Halal certification within the scope of modern society as it is today raises a bit of concern for some products that do not have a halal certificate. When reviewed in fiqh books, we will find al-tahrîm wal ihlâl haqqullâh wahdah. This is studied descriptively and qualitatively. There are three problems related to the issue of halal labeling which so far the rights are in the hands of the MUI. First, is the political problem caused by labeling itself. Second, is a religious issue. Third, related to economic matters. Abstrak Sertifikasi halal didalam lingkup masyarakat modern seperti sekarang ini menimbulkan sedikit kerisauan terhadap sejumlah produk yang tidak memiliki sertifikat halal. Apabila ditinjau dalam pustaka pustaka kitab fiqih, kita akan menemukan al-tahrîm wal ihlâl haqqullâh wahdah. Ini dikaji secara deskriptif dan bersifat kualitatif. Ada tiga masalah yang berkaitan dengan persoalan labelisasi halal yang dalam ini wilayah haknya ada di tangan MUI. Pertama, adalah masalah politis yang ditimbulkan soal labelisasi itu sendiri. Kedua, adalah masalah keagamaan. Ketiga, menyangkut soal ekonomi